Corporate social responsibility in Bolivia: Meanings and consequences - Boris Herbas Torrico; Björn Frank; Carlos Arandia Tavera (International Journal of Corporate Social Responsibility (JCSR), 2018)
Corporate social responsibility (CSR) has been studied extensively in developed countries. However, although most of the world's consumers live in developing countries, the study of CSR in developing countries in general, and in Bolivia in particular, still is very limited. Developing countries are characterized by widespread poverty, corruption, inequality, social exploitation, and environmental pollution and, consequently, offer abundant opportunities for CSR. In addition, research on CSR in developing countries has the potential to promote equality, social justice, transparency, and accountability by holding frequently irresponsible local and international organizations to account. For that purpose, this study explores the nature of CSR practices and their effectiveness in influencing consumer attitudes in Bolivia as the least developed among the developing countries in the Americas. To this end, this study uses data collected in Bolivia through both structured surveys (quantitative data) and unstructured questionnaires/in-depth interviews (qualitative data). Using structural equation modeling of the quantitative data on two product categories and multiple brand contexts from 1016 consumers, this study tests a series of hypotheses on the consequences of CSR practices in developing countries. The results indicate that CSR practices exert both a direct influence on customer satisfaction and an indirect, mediated influence on customer loyalty. Moreover, the results of qualitative data analysis suggest that multinational companies and young managers are leading the way in implementing CSR practices in Bolivia. Managerial implications are discussed.
Keywords: 650; Corporate social responsibility; Customer satisfaction; Customer loyalty; Developing country; Eco-friendly practices; Environmental sustainability; Ethical behavior; Latin America; Recycling convenience; Social sustainability